2017
DOI: 10.1039/c7cc00255f
|View full text |Cite|
|
Sign up to set email alerts
|

Quantifying and understanding the steric properties of N-heterocyclic carbenes

Abstract: This Feature Article presents and discusses the use of different methods to quantify and explore the steric impact of N-heterocyclic carbene (NHC) ligands. These include (a) the percent buried volume (%V), which provides a convenient single number to measure steric impact and (b) steric maps, which provide a graphical representation of the steric profile of a ligand using colour-coded contour maps. A critical discussion of the scope and limitations of these tools is presented, along with some examples of their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
231
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 316 publications
(244 citation statements)
references
References 92 publications
12
231
0
1
Order By: Relevance
“…À1.7 ppm), [8] whereas the dibromo derivatives appeared furtheru pfield, around À8ppm (Table 2), as expected from the less electron-withdrawing character of Br versus Cl. The 13 CNMR resonances of the boron-bound NHC and thienyl carbon atoms, broadened by coupling to the quadrupolar [25] d ( 31 P) [ppm] [22,26] %V bur [24] I Me Me H2 054. [8] andt ypicalo fC NHC ÀB sdonor interactions in sp 3 boranes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…À1.7 ppm), [8] whereas the dibromo derivatives appeared furtheru pfield, around À8ppm (Table 2), as expected from the less electron-withdrawing character of Br versus Cl. The 13 CNMR resonances of the boron-bound NHC and thienyl carbon atoms, broadened by coupling to the quadrupolar [25] d ( 31 P) [ppm] [22,26] %V bur [24] I Me Me H2 054. [8] andt ypicalo fC NHC ÀB sdonor interactions in sp 3 boranes.…”
Section: Resultsmentioning
confidence: 99%
“…The electronic properties of NHCs are commonly quantified by the Tolman electronic parameter (TEP), [21] which corresponds to the IR stretching frequency of the carbonyll igands in complexes of the form [Ni(CO) 3 (NHC)]: the more s-donating and/or less p-accepting the NHC ligand, the highert he value of the TEP.F urthermore,B ertrand and co-workersh ave shown that the 31 PN MR shifts of NHCp henylphosphinidene adducts provide ar eliable indicator of the relative p-acceptors trength of NHCs:t he more p-accepting the carbene ligand, the further downfield the 31 PN MR shift. [22] The steric properties of NHCs can be conveniently compared using the percentb uried volume( % V bur ), [23] defined here as the percentage of a3 .5 radius sphere around the metal center that is occupied by the ligand,a ssuming am etal-ligand distance of 2 .I Me ,I MeMe ((1,3,4,5-Me 4 )imidazol-2-ylidene), I iPr andI Mes were thus selected for their increasing steric bulk [24] and decreasing TEPs, [25] as well as fort he increased p-acceptor strength going from I Me to I MeMe to I iPr , [22,26] as summarized in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…[5] To our knowledge,t his represents the most sterically encumbering NHC to date and for comparison, the %V bur for the AuCl complexes of the widely used bulky NHCs IPr and IPr* are 45.4 and 50.4 %, respectively (Scheme 1). [6] The coordination profile of ITrw as investigated by the synthesiso favariety of 1:1a dducts (3)(4)(5), as summarized in Scheme 3. The Rh I carbonyl complex [(ITr)Rh(CO) 2 Cl] (5)w as used to extract an estimated donor strength of ITrr elative to previously reported carbenes by determination of the To lman electronic parameter (TEP).…”
mentioning
confidence: 99%
“…[19] According to the observed values at 2057 and 1975 cm À1 (CH 2 Cl 2 ; n av (CO) = 2016cm À1 ), the Tolman electronic parameter( TEP) of CAFeC was estimated to be 2044 cm À1 . [7b, 9a, 16] Finally,t he percentb uried volume (%V bur ) [21] and the steric map were calculated from the solid-states tructure of (R a ,R p )-8 to investigate the steric properties of 3 ( Figure 3). [7b, 9a, 16] Finally,t he percentb uried volume (%V bur ) [21] and the steric map were calculated from the solid-states tructure of (R a ,R p )-8 to investigate the steric properties of 3 ( Figure 3).…”
Section: Resultsmentioning
confidence: 99%